Ultra-Short-Pulse Laser Welding of Glass to Metal with a Shear Strength Above 50 MPa - Lukas Günther; Jens Ulrich Thomas; Jens Hermann; Axel Ohlinger; Dominique de Ligny (Micromachines)
We report an ultra-short-pulse laser welding process that allows one to consistently weld Borofloat® 33 glass to aluminum with a shear strength above 50 MPa. We explored the morphology of the welding seam and quantified the quality of the bonding by statistically determining the shear strength with more than 30 samples. The results of the shear strength tests indicate that the intrinsic shear strength of the aluminum serves as the upper limit of the glass-to-metal bond.